Narrative of Denial from Five Cases of the Incestuous Fathers - Titiek Kartika Hendrastiti; Noeke Sri Wardhani (Jurnal Perempuan, 2021)
Various data from the society show the tendency of increasing number of incest’s cases. This study aims to analyze the narratives of five cases of fathers who become perpetrators of incest. This study was conducted in 2016 to five fathers of incestuous perpetrators, who inhabited two Correctional Institutions in Bengkulu. This study was conducted using feminist narrative analysis and found that incestuous perpetrators rationalize their crimes based on their sexual identity and history to the victim. The history of the victims’ sexuality, which represents corrupted, dirty, wild, and naughty bodies, became a justification for incest. Persons with disabilities faced multiple vulnerabilities, not only being humiliated through the rape by their fathers, but they were also being blamed for their inability to participate in the investigation process and court hearings. The research has found linkages between incest and early marriage, troubled marriages, and early divorce. The construction of hypersexuality and the objectification of the perpetrators towards child sexuality had failed to guide the perpetrators towards a sane relationship.